2017
DOI: 10.1007/s00018-017-2714-7
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways and mesenchymal transition in pediatric high-grade glioma

Abstract: Pediatric high-grade gliomas (pHGG), including diffuse intrinsic pontine gliomas (DIPG), are the most lethal types of cancer in children. In recent years, it has become evident that these tumors are driven by epigenetic events, mainly mutations involving genes encoding Histone 3, setting them apart from their adult counterparts. These tumors are exceptionally resistant to chemotherapy and respond only temporarily to radiotherapy. Moreover, their delicate location and diffuse growth pattern make complete surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 267 publications
(245 reference statements)
3
53
0
Order By: Relevance
“…In line with this, EMT-associated pathways and transcription factors have been found activated in DIPG (41). Moreover, in adult GBM a higher incidence of TP53 mutation was observed in tumors with a diffuse compared to non-diffuse classification (42).…”
Section: Tp53supporting
confidence: 62%
See 1 more Smart Citation
“…In line with this, EMT-associated pathways and transcription factors have been found activated in DIPG (41). Moreover, in adult GBM a higher incidence of TP53 mutation was observed in tumors with a diffuse compared to non-diffuse classification (42).…”
Section: Tp53supporting
confidence: 62%
“…Indeed, this process has been heavily associated with malignant invasive and migratory behavior for many types of cancer (40). In DIPG, mesenchymal transition of glial cells, including the upregulation of mesenchymal related transcription factors and the induction of a mesenchymal phenotype could contribute to tumor invasion as well (41). Loss of TP53 is relatively common in DIPG (17) and, although not directly studied, could contribute to its invasive nature by promoting mesenchymal transition though SNAI1 (Figure 1B).…”
Section: Tp53mentioning
confidence: 99%
“…17 Intriguingly, GBM cells utilize the ability to undergo mesenchymal transition, either spontaneously, 18 or in response to radiotherapy. 19 In this study, we identified that CXCL1 is highly enriched in GBM and the elevation of CXCL1 is associated with radioresistance and poor prognosis in GBM patients. Additionally, knockdown of CXCL1 attenuated the proliferation and enhanced radiosensitivity of GBM cells.…”
mentioning
confidence: 80%
“…32 Acquired radioresistance characterizes a major cause of poor prognosis thus promotes tumor recurrence in GBM. 33 Various molecular pathways have been proved to be responsible for the acquisition of radioresistance, including EMT, 19 NF-κB, 34 and Wnt/β-catenin. 35 Accumulating data showed that CXCL1, a small cytokine expressed by macrophages, epithelial cells, and neutrophils, 36,37 was associated with therapy resistance in diverse subtypes of cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation